A new regularization of the D-bar method with complex conductivity. Issue 5 (4th May 2021) - El Arwadi, Toufic; Sayah, Toni
Abstract : The aim of the D-bar method is to solve inverse conductivity problems. For complex conductivity, Hamilton et al. presented a reconstruction method which consists of six steps. In this article, we present a new regularization denoted by S m based on an iterative algorithm which allows us to reconstruct an approximation of the conductivity of the domain. The advantage of this new regularization is the performance of high-order error estimates.